Determination of rainfall index for selected sites in Unimas campus - Mahinggil, Colin S. (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Rainfall phi index is one of the criteria of soil types which are on this situation, infiltration rate was in constant. It also can be said that this is the minimum rate that can be achieved by some soil types. Actually the main objective is for the purpose of estimating rainfall phi index values which is by using 'double ring infiltrometer' instrument. This instrument is used to determine infiltration rate into soil and then this data will plotted in graph which is against with time. From graph analysis, a constant value from the curve which is parallel with x axis win be obtained and actually this is the value phi index that has to be determined. From experiment that have been done, value of phi index that has been taken as an average value is 0.7 cm/hr which is it was in between silt loam and loam for it soil types. The range of minimum infiltration is between 0.67 cm/hr to 1.3 em/hr. Anyway, value of phi index that have been documented is small then phi index from design data. This is causes by several errors that occur during experiment.